(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This device is designed to measure the rate of oxygen saturation of the blood (blood oxygen) in addition to the heart rate. Method that is both effective and painless. The principle of the device’s work is mainly based on the max 03133 sensor, which consists of two optical transmitters (LED), one for infrared and the other for infrared, an optical receiver and optical lenses, in addition to a similar signal processor. The sensor emits beams of infrared and infrared rays. These beams must pass through the finger to reach the receiver. As it passes, some of it will be absorbed by the blood. The unabsorbed part reaches the photoreceptor. The amount of radiation absorbed by the blood changes according to the characteristics of the blood. Where it was found that oxygenated blood (Oxy Hb) absorbs infrared rays more than red rays, while deoxygenated blood (Deoxy Hb) behaves the opposite way. Because it absorbs more red rays than infrared rays, that is: the ratio of both oxygenated and deoxygenated blood can be determined to according to the ratio of red and non-red rays coming to the photoreceptor, and on this principle, the sensor measures the oxygen Content in the blood, while the pulse rate is measured based on infrared radiation. When the heart pumps blood, an increase in the oxygenated blood occurs due to the increase in blood, and as the heart relaxes, the volume of oxygenated blood decreases. By knowing the time between the increase and decrease in the oxygenated blood, the pulse rate is determined. The Arduino is connected to the max03133 sensor via the I2C protocol, which is a serial communication protocol and requires two wires to communicate. As for the second wire, it is called the Serial Clock Line or SCL, and it is responsiblefor transferring the clock signal from the Master to the Slave, then displaying the result on the LCD screen